1983
DOI: 10.1111/j.1095-8649.1983.tb04737.x
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐DNA ratio as an index to growth in salmonid fishes in the laboratory and in streams contaminated by carbaryl

Abstract: Free nucleotides, RNA, and DNA were extracted from fish white muscle and analysed by a two-wavelength ultraviolet (UV) absorbance technique to determine their relation to growth rates in brook trout, Salvelinus fontinalis, and Atlantic salmon, Salmo salar. In the laboratory, fish given ample feed had higher growth rates than fish on restricted rations, and these growth rates were significantly correlated with RNA-DNA ratios. Wild brook trout from natural streams had higher average RNA-DNA ratios than those in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 9 publications
4
24
0
1
Order By: Relevance
“…The RNA index was found to be most sensitive when concentration was expressed per unit dry weight rather than as the RNA:DNA or RNA:protein ratios. These findings agree with those of a number of workers who recorded increased variability when RNA was expressed as a ratio in both fish (Wilder & Stanley 1983, Ferguson & Danzmann 1990) and crustaceans (Moss 1994a,b). Similarly, Houlihan et al (1998) found that in the cephalopod Eledone cirrhosa the RNA concentration per unit fresh weight showed a higher correlation with growth rate than the RNA:protein ratio.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The RNA index was found to be most sensitive when concentration was expressed per unit dry weight rather than as the RNA:DNA or RNA:protein ratios. These findings agree with those of a number of workers who recorded increased variability when RNA was expressed as a ratio in both fish (Wilder & Stanley 1983, Ferguson & Danzmann 1990) and crustaceans (Moss 1994a,b). Similarly, Houlihan et al (1998) found that in the cephalopod Eledone cirrhosa the RNA concentration per unit fresh weight showed a higher correlation with growth rate than the RNA:protein ratio.…”
Section: Discussionsupporting
confidence: 82%
“…These were a modification of the diphenylamine method (Burton 1956) and the dual wavelength method (Wilder & Stanley 1983). Samples (50 mg) of tissue and standards (calf thymus DNA, Sigma) were placed in centrifuge tubes to which 5 ml of 0.5 N PCA were added and the tubes were heated at 70°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, RNA-DNA ratios in rohu spawn were positively correlated to the trends in growth as has been indicated by several authors (Bulow 1970(Bulow , 1971Haines 1973Haines , 1980Bulow et al 1981). Wilder and Stanley (1983) confirmed the relationship be tween growth and RNA-DNA ratios in brook trout, Salvelinus fontinalis and Atlantic salmon, Salmo salar. In the present study, the elevated RNA-DNA ratios were associated with higher levels of RNA and lower levels of DNA.…”
Section: Discussionsupporting
confidence: 72%
“…To test whether the growth ability of juveniles differed between group 1 and 2, we analysed indices of RNA/DNA. The correlation between growth rate and RNA/DNA ratio in muscle tissue has been demonstrated for several species of fish (Bulow 1970, Haines 1980, Wilder & Stanley 1983, Nakano et al 1985. The RNA/DNA ratio may be used as a criterion of growth rate because tissue protein growth is accompanied by intensive synthesis of RNA, whereas the total DNA level has a tendency to remain constant.…”
Section: Methodsmentioning
confidence: 99%